Plano de testes para aplicação em sistemas embarcados com arquitetura orientada a serviços - Martins, Vinícius Farias (Universidade Federal de São Carlos, 2026)
A software engineering project requires a good understanding of the system being created so that tests can be executed more efficiently. With the increasing complexity of embedded systems projects in recent decades, it is important to have a well-defined testing phase to effectively validate the software and hardware components of an embedded system. This work proposes an organized test plan, for considerable optimization of development time, which can be replicated for use in any embedded system built using service-oriented architecture. The master testing approach presented in this work has a defined order of documentation and execution to ensure that all types of tests are performed in an organized manner. The test plan was executed on the AGV AD01, from the Tear laboratory of the Federal University of São Carlos, in order to obtain results on the vehicle's operation, such as the wheel control system, the automatic correction of path errors, and the behavior of the parameters involved in the system as a whole. An analysis of the results was also performed to understand the errors found and make the necessary corrections.
Test plan for application in service-oriented architecture embedded systems
Keywords: Arquitetura orientada a serviços; Automação; Engenharia de software; Engenharia de testes; Sistemas embarcados; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; 9. Indústria, Inovação e Infraestrutura